Estimativas de parâemtros genéticos para características morfométricas em cavalos Quarto de Milha de corrida - Pereira, Guilherme Luis [UNESP]; Meira, Camila Tângari [UNESP]; Silva, Josineudson Augusto II de Vasconcelos [UNESP]; Chardulo, Luis Artur Loyola [UNESP]; Curi, Rogério Abdallah [UNESP] (My University, 2014)
With highlighted sprint ability, the racing line is important segment within the Quarter Horses breed, with huge impact on agribusiness. Theseanimals have noted morphological differences when compared to other lines within the breed, especially for larger body size proportions.The objective of this study was to estimate genetic parameters forbody measurements traitsof the racing line of the Quarter Horses breed via Bayesian inference. Here,289 animals of both sexes, registered at brazilian association of breeders (ABQM), were used. The results showed high coefficient of heritability for body length (0.74) and back-loin lenght(0.61). The heritability coefficients for height at withersand croup length were moderate (0.44 and 0.47, respectively). High genetic correlation for body length and croup length and for body length and back-loins lengthwas also observed(0.80 and 0.76, respectively). Taking into account the estimates of heritability and genetic correlations between body measurement traits, the body length and height at withers traits proved to be appropriate to provide future researches that investigate the genetic correlation between body measurements and racing performance. Keywords: Heritability, Correlation, Length, Heigth.
Estimates of genetic parameters for body measurement traits in quarter horses of racing
Keywords: Heritability; Correlation; Length; Heigth